The Production and Fate of Volatile Organosulfur Compounds in Sulfidic and Ferruginous Sediment. Issue 11 (13th November 2019) - Wilkening, Jean V.; Turchyn, Alexandra V.; Redeker, Kelly R.; Mills, Jennifer V.; Antler, Gilad; Carrión, Ornella; Todd, Jonathan D.
Abstract: Volatile organic sulfur compounds (VOSCs) link the atmospheric, marine, and terrestrial sulfur cycles in marine and marginal marine environments. Despite the important role VOSCs play in global biogeochemical sulfur cycling, less is known about how the local geochemical conditions influence production and consumption of VOSCs. We present a study of dimethyl sulfide (DMS), methanethiol (MeSH), and dimethylsulfoniopropionate (DMSP) in sulfide‐rich (sulfidic) and iron‐rich (ferruginous) salt marsh sediment from north Norfolk, UK. Initial results illustrate the importance of minimizing time between sampling in remote field locations and laboratory analysis, due to rapid degradation of VOSCs. With rapid analysis of sediment from different depths, we observe high concentrations of DMS, MeSH, and DMSP, with concentrations in surface sediment an order of magnitude higher than those in previous studies of surface water. We measure systematic differences in the concentration and depth distribution of MeSH and DMS between sediment environments; DMS concentrations are higher in ferruginous sediment, and MeSH concentrations are higher in sulfidic sediment. With repeated measurements over a short time period, we show that the degradation patterns for DMS and MeSH are different in the ferruginous versus sulfidic sediment. We discuss potential biogeochemical interactions that could be driving the observed differences in VOSC dynamics in ferruginous and sulfidic sediment. Plain Language Summary: Oceans and coastal wetlands are dynamic environments where the carbon, sulfur, and iron biogeochemical cycles are tightly coupled. One important process that occurs in these environments is the formation of organic sulfur gases, which are involved in cloud formation and acid rain. Organic sulfur gases can be formed through a number of biological and chemical pathways, but little is known about how environmental conditions influence the chemical and microbial reactions that form these gases. In this study, we investigate how different chemical environments in salt marsh sediment influence the formation and destruction of organic sulfur gases. Different organic sulfur gases are produced in iron‐rich environments compared to those produced in sulfide‐rich environments. Further, the two geochemical environments also showed different patterns in the breakdown of these gases. These results indicate that the geochemical conditions influence how organic sulfur gases form and how they are released to the atmosphere. These findings have the potential to help explain observed differences in the release of organic sulfur gases among modern‐day environments, as well as how the release of organic sulfur gases may have changed throughout Earth history as environmental conditions evolved. Key Points: Rapid analysis reveals high concentrations of dimethyl sulfide, methanethiol, and dimethylsulfoniopropionate in salt marsh sediment Sulfidic sediment contained higher concentrations of methanethiol, and dimethyl sulfide concentrations were higher in ferruginous sediment There are different degradation patterns for dimethyl sulfide and methanethiol based on the geochemistry of the environment